Study of accumulation of some heavy metal content in two species of algae (Corallina officinalis, Laurencia elata) in the littoral zone of Lattakia (Latakia University Journal -Biological Sciences Series, 2021)
Heavy metals in water are accumulated in living organisms through the food chain, starting from algae and ending by fish,  which is considered an important source of food for humans. Therefore, this study aimed to estimate the concentration of heavy metals (Zn, Cu, Pb and Cd) in the water of two locations (Ras Alshamra and Ras Ibn Hani) on the shore of Lattakia City and in two algae species (Corallina officinalis, Laurencia elata). The results showed a significant difference in the concentration of heavy metals in the water of the two locations, where Ras Ibn Hani had higher  concentrations than Ras Alshamra. This differences in concentrations are due to the presence of various human activities and to a higher number of fishing boats in Ras Ibn Hani comparing to Ras Alshamra. The analysis of algae species showed a higher level of heavy metals in Laurencia elata than the level in  Corallina officinalis. The comparison of heavy metal concentrations between water and algae showed similar patterns. Zn was present in the highest concentration while Cd was in the lowest one. The concentration of heavy metals showed the following order: Zn> Pb> Cu> Cd.